Estratégia e processos de gestão em Call Centers próprios e terceirizados no Brasil - Melo, Pedro Lucas de Resende (2007)
This dissertation comes from an international survey on the call center industry. Specifically this dissertation discusses about the strategy and practices of human resources in the call center industry in Brazil. We investigate if a relationship exists among the outsourcing, the strategy of the call center and the allocation of the strategic human resources of those companies in the Brazilian call centers. The following hypothesis are developed: The outsourced call centers are guided to the attendance of a mass segment (H1a), with a strategy targeted to the product/service (H1b). (H2): In the outsourced call centers in which the strategy is targeting to the product/service the main strategic resource is the technology of the information. (H3a): In the in-house call centers in which the strategy is targeting the customer, the main strategic resource it is the human resource. (H3b): In in-house call centers where the strategy is focused in the customer, the attendants receive more intensive trainings. (H3c): In in-house call centers where the strategy is focused in the customer, the attendants have more autonomy in the performance of their activities. Through the multivariate analysis of regression logistics the hypothesis are tested in a sample that represents about 50% of the call centers associated to ABT (Brazilian Association of Tele-Services). The hypothesis are confirmed through the model with high explanation power (R2=46%) showing that the outsourced call centers are guided for mass segments, while in-house call centers are targeted for specific segments using as the main strategic resource the human resources